PENERAPAN MOTIF TRENGGILING PADA KERIS DHAPUR BETOK PAMOR UDAN MAS - Ari Harmawan; Kuntadi Wasi Darmojo (Ornamen, 2022)
Traditional weapons, especially kris, have developed from their shape and character along with the times. In this final project, the writer makes a new keris, combining the pangolin motif on the kris with the chopping technique in the work. The Pangolin motif gives inspiration to the author, because it has a shape on the scales that is attractive and represents a symbol of self-protection. Pangolins are the only mammals that have scales to protect themselves from predators or predators in the wild. The pangolin motif is adapted to the design and will be applied to tosan aji's work in the form of a kris. The creation methods applied in the creation process are the exploration stage, the design stage, and the embodiment stage. Exploration includes observations, literature study and interviews. The design includes analysis and alternative sketches. The embodiment includes the application of the material that is in accordance with the selected sketch, which produces three kris, namely: Dhapur Trenggiling Sisik Waja, Dhapur Trenggiling Lingkaring Urip, Dhapur Manis Javanica. The creation of this final project rests on the application of the Pangolin motif to the kris using the tinatah technique. The Pangolin motif inspires the writer, because it has an interesting, unique character, and represents a symbol of self-protection. It is hoped that they will produce new kris creations without leaving the tradition that can build the meanings and help preserve works of art.